IgE re-programs alternatively-activated human macrophages towards pro-inflammatory anti-tumoural statesResearch in context - Giulia Pellizzari (EBioMedicine, 2019)
Background: Antibody Fc-driven engagement of macrophages is critical for evoking cellular activation and effector functions and influencing tumour-associated macrophage (TAM) recruitment. We previously reported that IgE class antibodies promote restriction of cancer growth in rodent models associated with significant TAM infiltration. However, the human macrophage-associated IgE-Fc Receptor (FcεR) axis remains unexplored. We investigated the effects of anti-tumour IgE stimulation on human macrophage activation. Methods: Human blood monocyte-differentiated quiescent (M0), classically-(M1) and alternatively-(M2) activated macrophages were crosslinked with IgE and polyclonal antibodies to mimic immune complex formation. We examined surface marker expression, cytokine secretion, protein kinase phosphorylation and gene expression in IgE-stimulated macrophages and IgE antibody-dependent macrophage-mediated cytotoxicity (ADCC) against tumour cells. Findings: A proportion (40%) of M2 and (<20%) M0 and M1 macrophages expressed the high-affinity IgE receptor FcεRI. IgE crosslinking triggered upregulation of co-stimulatory CD80, increased TNFα, IFNγ, IL-1β, IL-12, IL-10, IL-13, CXCL9, CXCL11 and RANTES secretion by M0 and M2 and additionally enhanced MCP-1 by M2 macrophages. IgE-stimulated M1 macrophages retained secretion of pro-inflammatory cytokines. IgE crosslinking enhanced the FcεRI-dependent signalling pathway, including phosphorylation of the Lyn kinase, ERK1/2 and p38 in M2 macrophages and upregulated Lyn gene expression by M1 and M2 macrophages. Anti-tumour IgE engendered ADCC of cancer cells by all macrophage subsets. Interpretation: IgE can engage and re-educate alternatively-activated macrophages towards pro-inflammatory phenotypes and prime all subsets to mediate anti-tumour functions. This points to IgE-mediated cascades with potential to activate immune stroma and may be significant in the clinical development of strategies targeting tumour-resident macrophages. Keywords: Cancer immunotherapy, Pellizzari et al.